Weakening of Peridotite Sheared at Hydrothermal Conditions. (28th October 2021) - Moore, Diane E.; Lockner, David A.
Abstract: We conducted triaxial friction tests at hydrothermal conditions (25°C–350°C) on gouges of peridotite and its principal mineral constituents olivine and orthopyroxene. Pore‐fluid chemistry was varied by the use of peridotite, granite, or quartzite driving blocks (representing wall rock) housing the gouge layer. Samples sheared at slow rates initially strengthen to a peak value, and then weaken toward a residual strength. The transition is accompanied by a change from velocity‐weakening to velocity‐strengthening behavior marked by a series of small stress drops. The extent of weakening varies with the ultramafic mineralogy and with the chemical environment established by the driving block lithology. The strengths of olivine and olivine‐rich peridotite gouges decrease substantially (to μ  ∼ 0.25–0.30), and that of orthopyroxene to a lesser extent, at temperatures ≥200°C when sheared between crustal driving blocks. Less weakening is observed in the peridotite‐block experiments; the minimum strength of the peridotite gouges ( μ  ∼ 0.5) occurs at 250°C, the temperature at which olivine hydration rates are near their maximum in ultramafic rocks. The strength reductions in all experiments are attributed to solution‐transfer (pressure solution) processes that come to predominate over cataclastic mechanisms during shear. The lower pH of fluids in contact with silica‐saturated crustal rocks enhances the weakening of olivine‐rich gouges. In these short‐duration experiments, secondary phyllosilicate mineral growth was of a limited extent and varied with gouge and wall‐rock mineralogy and with temperature. Over geologic time spans, however, the alteration assemblages will assume an increasingly important role in fault‐zone behavior. Plain Language Summary: The minerals in mantle rocks, which form at considerable depths in the Earth, generally are not stable when the rocks are brought to shallower depths by processes of erosion or of uplift along faults. These minerals will dissolve in heated groundwaters and new minerals will crystallize to replace them. We ran frictional strength experiments on samples of one of these mantle rock types to see how such dissolution‐crystallization reactions might affect the behavior of a newly generated, fluid‐filled fault. We found that the rocks gradually weakened with increasing displacement over time, and their sliding behavior changed from being capable of generating earthquakes to stable slip that will tend to suppress earthquakes. The amount of strength reduction was controlled by the dissolution rates of the minerals at different conditions of temperature and fluid chemistry. The results of these experiments will contribute to the assessment of earthquake hazards along active faults cutting through such rocks and further our understanding of fault‐zone behavior. Key Points: Peridotite gouge weakens and transitions from unstable to stable slip when sheared at hydrothermal conditions Weakening occurs by a solution‐transfer creep process that is promoted by the relatively high dissolution rates of the ultramafic minerals The amount of strength reduction varies with fluid chemistry